PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PENGGUNA JASA TRANSPORTASI TAKSI NEW ATLAS KOTA SEMARANG - Luqmananda Bayuningrat; Handoyo Djoko Waluyo; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2014)
NEW ATLAS GROUP is one of company that is concern in providing taxi transportation services inSemarang. The research itself aims to determine of the influence of Service Quality (X1), Product Quality (X2),Customer Satisfaction (Z) of the Customer Loyalty (Y) New Atlas Taxi’s. This type of research used is explanatoryresearch, data collection methods using an oral interview and a data collection tool using a questionnaire with asample of 100 respondents New Atlas Taxi users of transport services via nonprobability sampling technique byusing purposive sampling method (sampling technique based on certain conditions). The analysis technique uses testvalidity, test reliability, simple linear regression, multiple linear regression, t test and F test with SPSS 20 tool.From the data analysis it can be concluded that amounted to 61.8% customer satisfaction variables can beexplained by service quality variable and 57.1% explained by product quality variable. 15.2% customer loyaltyvariable can be explained by service quality variable and 15.4% explained by the variable quality product quality.Customer satisfaction being a mediator to customer loyalty due to the indirect effect by 26.7% of the service qualityvariable and product quality variables. The suggestion in this research is the company management is necessary togive directions the driver to pay more attention to the quickness and timeliness of delivering passengers to theirdestination, more discipline the taxi driver in order to obey the standard service procedure that has beenestablished, providing complaint and suggestion boxes for each passenger in the taxi fleet.